Level of awareness on Malaysia stock market : a case study of University Technology Mara / Muhammad Mahathir Yahaya and Nur Farraheeda Roslan - Yahaya, Muhammad Mahathir; Roslan, Nur Farraheeda (Faculty of Business and Management, 2013)
The concept of the study level of awareness among UiTM students on stock market is based on Attention-Interest-Desire-Action, which are to discover the comprehension and understanding of respondents towards Malaysian stock market. The factor of independent variable (Attention, Interest, Desire and Action) towards level of awareness are been used on this study. The distribution of structured and online questionnaire are been used to collect the infonnation needed from the respondent. Then, the questionnaire were analyzed and interpreted using SPSS software Version 21 which is the latest program. Each of the variable were tested by several analysis such as Pearson Correlation to fmd the relationship between dependent and independent variable. On the other hand, the results indicate the significant of the variable and meet the objective of the research. After the study held, researchers raised several opinions and recommendation ofthe study that awareness on the investment very essential because it can shape our future fmancial.